Kemulariella tahirelcii (Asteraceae; Astereae), a new species from Şırnak, Turkey - Firat, Mehmet (Phytotaxa, 2016)
Kemulariella tahirelcii Fırat, a new species from Şırnak, Turkey, is described and illustrated. It is a perennial, obligate chasmophyte that occurs in the cracks of limenstone blocky cliffs. This species is similar to K. colchica, from which it clearly differs mainly in a lesser number of flowers in the capitula, and in shorter ray and disc florets. The new species is a local endemic of the Cudi Mountain, south-eastern Turkey, being ‘Vulnerable’ (VU) [criteria B2b (i,ii,iii)] due to its narrow distribution.